Seafood processing : - Venugopal, V. (Taylor & Francis, 2005)
With global fish production falling behind demand, the aquaculture of selected species has become an effective method to augment fish availability. Unlike natural species, however, cultured fish have limited consumer appeal. Value addition techniques can not only help satisfy the rising consumer demand for processed fishery products but also enhance the acceptability of aquacultured fishery products and help many countries develop their international seafood trade.